Analysis Use Preposition VON and AUS In Indonesian - Anggraini, Vita; Nnko, Godwin Ulick; Zikri, Mona (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study : Research This aiming For understand the meaning produced by the preposition von and aus in various situation communication . Pragmatics focus on usage Language in context real , so that can give outlook about How preposition This used For convey appropriate meaning​ with situation communication. Methodology: Research This use method descriptive qualitative For analyze preposition from and worn out in Indonesian . Data obtained from text translation , interview informants , and observations conversation . Analysis covers data reduction , classification function preposition , interpretation contextual , and triangulation For ensure validity results . Main Findings: Research This find that von more often used for show origin or connection ownership, while aus referring to the material or origin physical. Error translation often happen consequence translation literally, as in the sentence I am like that from Germany , which is more appropriate translated as